Answer:
-12
Explanation:
y = 4x^2 + 8x - 8
Put brackets around the first 2 terms and pull out the common factor
y = (4x^2 + 8x) - 8
y = 4(x^2 + 2x) - 8
Take 1/2 of the linear term (2x) and square it. Put the square inside the brackets.
y = 4(x^2 + 2x + (2/2)^2 ) - 8
y = 4(x^2 + 2x + 1) - 8
You have added 4*1 inside the brackets. You must subtract that amount outside the brackets.
y = 4(x^2 +2x + 1) - 8 - 4
Notice that the trinomial inside the brackets is a perfect square. Combine the terms outside the brackets.
y = 4(x + 1)^2 - 12
You have completed the square and you are finished.
The vertex is (-1, - 12)
The y value is - 12.
Just to confirm this, I have included the graph.